Enhancing English Speaking Proficiency through Video Assignments: Addressing Linguistic and Psychological Challenges among Indonesian EFL Students - Rohmiyati, Yuli; Imron, Ali; Asiah, Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
In a globally interconnected society, being able to communicate effectively requires language skills, especially in English. Speaking ability is the most crucial language ability, particularly for English as a Foreign Language (EFL) students. This literature review study explores the challenges faced by Indonesian English learners in developing their speaking skills and proposes solutions to overcome these obstacles. It emphasizes the critical role of speaking in language acquisition and highlights linguistic challenges such as grammar, vocabulary, and pronunciation, as well as psychological challenges including lack of confidence, fear, and anxiety. Additionally, the lack of opportunities to practice speaking English is identified as a significant problem. To address these issues, the study discusses the use of video assignments as an effective tool to enhance speaking skills. This research aims to help students become more confident and proficient English speakers, offering valuable insights for educators and learners alike. The result shown that the students can reduce the speaking problems effctively through making video assignment.